Stx Gene In Escherichia Coli Isolates Of Pork And Buffalo Meat Origin - Chhabra, Daljeet; Kunal, K.K.; Chhabil , S.; Barbuddhe , S.B. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Thirty six E. coli isolates recovered from pork meat and twenty nine E. coli isolates recovered from buffalo meat were characterized for Stx gene. The PCR assay was standardized and the primer set for this gene allowed for amplification of 584 bp. Out of 36 isolates 15 (41.7%) were positive for Stx gene from pork samples and out of 29 isolates 15 (51.7%) for Stx gene from buffalo meat samples.
Keywords: E. coli; Stx gene; buffalo meat; pork